Heterogenous Behavioral Expectations, FX Fluctuations and Dynamic Stability in a Stylized Two-Country Macroeconomic Model - Christian R. Proa\~no (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2009)
In this paper the role of behavioral forecasting rules of chartist and fun-damentalist type for the dynamic macroeconomic stability of a two-country system is investigated both analytically and numerically. The main result of the paper is that for large trend-chasing parameters in the chartist rule used in the FX market, not only this market but the entire macroeconomic system is destabilized. This takes place despite of the presence of monetary policy rules in both countries which satisfy the Taylor Principle.
urn:nbn:de:101:1-2009071368
Keywords: E12; E31; E32; F41; 330; (D)AS-AD; monetary policy; behavioral heterogenous expectations; FX market dynamics.